3D face recognition using multiple features for local depth information - Khalid, Fatimah; N. A., Lili (2009)
In this paper, we recognized multiple features from the local depth information of distance and angle calculation. These features are calculated from the twelve salient points by considering the distance and angle calculation. Then, fifty three non-independent features are extracted and the discriminating power is used for analyzing these features. The result shows an improvement compared to the previous work